Crohn’s disease-associated interstitial lung disease mimicking sarcoidosis: a case report and review of the literature - Thao, Choua; Lagstein, Amir; Allen, Tadashi; Dincer, Huseyin Erhan; Kim, Hyun Joo (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Respiratory involvement in Crohn’s disease (CD) is a rare manifestation known to involve the large and small airways, lung parenchyma, and pleura. The clinical presentation is nonspecific, and diagnostic tests can mimic other pulmonary diseases, posing a diagnostic challenge and delay in treatment. We report a case of a 60-year-old female with a history of CD and psoriatic arthritis who presented with dyspnea, fever, and cough with abnormal radiological findings. Diagnostic testing revealed an elevated CD4:CD8 ratio in the bronchoalveolar lavage fluid, and cryoprobe lung biopsy results showed non-necrotizing granulomatous inflammation. We describe here the second reported case of pulmonary involvement mimicking sarcoidosis in Crohn’s disease and a review of the literature on the approaches to making a diagnosis of CD-associated interstitial lung disease.